The Juridical Analysis of Inheritance Distribution for Non-Muslim Heirs Muslim Heirs Conception of Legal Certainty - Annisa, Fitriana Nur (TABELLIUS: Journal of Law, 2023)
Indonesian society is a plural society in which two or more elements coexist and mingle with one another. In any society, every marriage cannot be separated from the possibility of producing offspring or children who are considered to be the bringers of happiness. With these facts, of course it will affect several sectors in Indonesia. In the legal field for example. The law most affected by diversity is the Law of Inheritance. That is, if the heirs are subject to Islamic inheritance law while there are Islamic heirs of different religions (non-Islam). In this study, researchers used a sociological juridical approach. Because the research that is sought is legal aspects in the implementation of the law with the implementation of science and applicable legal rules as well as from a social and community point of view in everyday life. The research specifications shown are descriptive analysis in nature. Researchers in their efforts to collect data are carried out in several ways, namely: field studies and studies of documents/library materials. According to western inheritance law, heirs of different religions are not a barrier to becoming heirs while Islamic inheritance law, heirs of different religions is a barrier to becoming heirs. However, heirs of different religions can still receive inheritance through a mandatory will as stipulated in the MA Jurisprudence No. 51/K/AG/1999 with the condition that it does not exceed 1/3 of the total inheritance.Keywords: Different; Inheritance; Religions.